Largely enhanced triboelectric nanogenerator for efficient harvesting of water wave energy by soft contacted structure. (March 2019) - Cheng, Ping; Guo, Hengyu; Wen, Zhen; Zhang, Chunlei; Yin, Xing; Li, Xinyuan; Liu, Di; Song, Weixing; Sun, Xuhui; Wang, Jie; Wang, Zhong Lin
Abstract: Triboelectric nanogenerator (TENG) is a new emerging and cost-effective technology for harvesting water wave energy because of its unmatchable performance in low frequency and randomly directed motions. Here, we report an approach that significantly increased the output power of spherical TENGs by optimizing both materials and structural design. Fabricated with an acrylic hollow sphere as its shell and a rolling flexible liquid/silicone as the soft core, the soft-contact spherical triboelectric nanogenerator (SS-TENG) presents up to 10-fold enhancement to the maximum output charge compared to that of a conventional Polytetrafluoroethylene (PTFE) based hard-contact one, which is resulted from the significantly increased contact area. Besides, the output is tunable through controlling the softness of the liquid/silicone core. Our finding provides a new optimization methodology for TENGs and enable its more promising usage in harvesting large-scale blue energy from water wave in oceans as well as feeble but ubiquitous wind energy. Graphical abstract: fx1 Highlights: Silicone rubber is used to improve the triboelectric outputs, silicone rubber. Soft-surface-contact largely improve transferred charges by increasing contact area. The maximum transferred charge can reach 500 nC, 10 times than the conventional value. The parameter of the structure can be turned to match the outside impact frequency. It is a practical and solid progress of TENG for harvesting low-frequency energy.